Development of the electric sector in Brasil, in Santa Catarina and its influences in the industrialization process (PerCursos, 2022)
Electric energy was one of the main pillars of the Second Industrial Revolution, causing social, economic and environmental changes, allowing the development of industry, the occasional participation of peripheral countries in international production, urbanization and new means of transport. It has become fundamental for economic/industrial development. In view of this, we investigated how Brazil and the state of Santa Catarina reacted to this reality. We seek to analyze the role of the electric sector in the industrial/economic formation of Santa Catarina, based on a historical rescue, from the perspective of socio-spatial formation. It is a research based on bibliographic consultations, on-site observations, debates and technical visits.
Keywords: eletricity; Santa Catarina; Brasil; industrialization